(untitled) (GAIMS Journal of Medical Sciences, 2026)
Non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) is a recently recognized thyroid tumor that mimics papillary thyroid carcinoma (PTC) but demonstrates an indolent course and excellent prognosis. Accurate diagnosis is critical to prevent overtreatment. We report a 20-year-old female with a gradually enlarging, painless midline neck swelling. Fine needle aspiration cytology (FNAC) performed twice yielded results suspicious for malignancy (Bethesda category V). Ultrasonography revealed a well-defined encapsulated nodule in the left lobe of the thyroid, categorized as TIRADS grade 3. CT imaging confirmed a circumscribed lesion with cystic and calcific foci, exerting mild pressure on adjacent vessels but without infiltration or lymphadenopathy. Based on these findings, a total thyroidectomy was performed. Gross examination revealed a tan-colored, encapsulated lesion measuring 2 × 1.5 × 1.4 cm. Histopathology demonstrated nuclear features of PTC with occasional psammoma bodies but no capsular/vascular invasion, papillary structures, tumor necrosis, or mitotic activity. A final diagnosis of NIFTP was made. NIFTP poses a diagnostic challenge due to its cytological and radiological overlap with thyroid carcinoma. Awareness of this entity is crucial to avoid unnecessary aggressive treatment. Lobectomy is usually sufficient, but total thyroidectomy may be performed due to preoperative diagnostic uncertainty.